If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 32 = 7t + -15t Combine like terms: 7t + -15t = -8t 32 = -8t Solving 32 = -8t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '8t' to each side of the equation. 32 + 8t = -8t + 8t Combine like terms: -8t + 8t = 0 32 + 8t = 0 Add '-32' to each side of the equation. 32 + -32 + 8t = 0 + -32 Combine like terms: 32 + -32 = 0 0 + 8t = 0 + -32 8t = 0 + -32 Combine like terms: 0 + -32 = -32 8t = -32 Divide each side by '8'. t = -4 Simplifying t = -4
| 4(2s+1)-5=6s | | -8z=16 | | 6x+5=-51-8x | | 26-x=4(x+4) | | p^2-p+1=0 | | 3*x-2*6-2=7x-4 | | -5x+8y=14 | | -6(x+3)-11=17+8 | | 10x=8-(-2) | | 3(x-2)-2=7x-4 | | 33-18=3(x-8) | | 6x-10y=80 | | 6x+14=-103-7x | | 22=y-10 | | 3w-5w=-10 | | 7(X-5)+15X= | | -x^2+3=(2x-1)(2x-1) | | (X+3)3+(x+4)4=8x | | -2x^2+10x-12= | | 0.4x-1.1(0.5-0.6x)=0.4 | | y+1=-2+3 | | x^2+7x-12= | | 5y-3=17+9y | | -8c+3=-37 | | 6r-13=-9+8r | | 6x-13=-9+8r | | 13(x-5)=-5-8 | | 5(3+3x)-4=101 | | 13x(x-5)=-5-8 | | 2a^2+3a+1=0 | | -5-6=-9+x | | 2(x+2)=7(x-1)+24 |